ANALISIS PENENTUAN RUTE DISTRIBUSI PASIR BETON SECARA OPTIMAL DENGAN METODE SAVING MATRIX PADA TB. HEHE - Cassandra Anisya Fadillah (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The increasing need for construction materials requires companies to manage the efficient distribution of concrete sand building materials. The main problem in distribution is the determination of the optimal delivery route so that transportation costs can be reduced without reducing the timeliness and load capacity of the vehicle. This study aims to determine the optimal distribution route of concrete sand using the Vehicle Routing Problem approach with the Saving Matrix method in TB. Hehe in the city of Bandung. The research was conducted through quantitative and qualitative approaches through observation, interviews, and documentation. Primary data is in the form of existing routes, distances between customers, cargo volume, and vehicle capacity on May 10, 2023. The analysis uses distance matrix calculations, distance savings matrices, and the preparation of alternative routes and actual distances with Microsoft Excel and Google Maps. The results showed that there was no savings in distribution mileage, before the optimization of 103 kilometers and after the application of the Saving Matrix method to 107 kilometers. However, there was a reduction in the number of routes from 10 routes to 5 routes including two routes that were able to optimize truck capacity by 100 cubic meters in one delivery on the route. In terms of cost, there is a fuel saving of Rp. 91,000 per day by combining the destination location in one route.